Therapeutic Communication Strategy in Social Isolation Patient: A Case Study of Mental Health Nursing - Suhanda; Ali Apriansyah; Herni Oktriani; Andan Firmansyah; Vikri Haikal Ramdani (Genius Journal, 2022)
Objective: To provide nursing care for socially isolated patients with therapeutic communication strategies for socially withdrawn patients. Methods: The method used is descriptive qualitative with a case study approach. The sampling technique is a therapeutic communication strategy. The sample taken was 1 patient who experienced social isolation disorders. The participants used in this study were the patient Mrs. S is 36 years old, a woman with social isolation mental disorders. The process of assessing and establishing a diagnosis is focused on the main problem. Objective and subjective data becomes a reference for periodic evaluation of nursing implementation. The location of the research was carried out at the BLUD of the Banjar City Hospital on 25-28 May 2022. Results: Based on the results of nursing care found signs and symptoms, namely with subjective data feeling lonely, feeling useless, verbal responses are lacking and very brief, while objective data is the client looks a lot silent and doesn't want to talk, facial expressions are less radiant, less eye contact. The nursing problem found is social isolation. The intervention given is therapeutic communication. Conclusion: Intervention of therapeutic communication strategies to help clients converse and want to get acquainted with their roommates in social isolation patients. This can happen if the patient can focus on doing therapeutic communication.